Performance of wood bottom ash as a replacement for Portland cement in coating mortars - Leila Celin Nascimento; Gercyr Baptista Junior; Gustavo de Castro Xavier; Afonso Rangel Garcez de Azevedo; Sergio Neves Monteiro; Carla Therezinha Dalvi Borjaille Alledi (Journal of Materials Research and Technology)
An alternative residue that offers sustainable benefits for the environment can partially replace cement in mortars used in construction. These residues are mainly agro-industrial waste and are generated in various industrial furnaces. Among them, the wood bottom ash stands out. The use of wood bottom ash is still an underexplored alternative regarding its influence on the specific properties of rendering mortar. Thus, the objective of this study is to evaluate the influence of wood bottom ash on the physical and mechanical properties of coating mortars, with partial replacements of Portland cement. The mortars were produced in a 1:3 ratio, in mass, and the replacement percentages used were 0%, 5%, 10%, and 15%. The replacement percentage that showed the best performance was 5%. In this percentage, the properties of consistency, bleeding, water absorption by capillarity, shrinkage and porosity were negatively affected. The properties that did not have significant change were: bulk density, air content, water retention, squeeze flow, flexural strength, pull-off strength, and dry bulk density. However, the properties that showed improvement were the setting time and the dynamic elastic modulus. Moreover, it was noticed by the calorimetry analysis that the 5% WBA replacement mortar favored nucleation during hydration. No differences in crystallinity were recorded compared to the reference mortar. Thus, from the analysis of experimental results, it was concluded that the application of a replacement percentage of 5% does not significantly alter the mechanical properties of the coating mortar, making it a promising destination for this waste.